2019
DOI: 10.3390/ncrna5020034
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNAs and the Innate Immune Response

Abstract: Innate immunity provides the initial defence against infection and it is now clear that long non-coding RNAs (lncRNAs) are important regulators of this response. Following activation of the innate response, we commonly see rapid induction of these lncRNAs and this is often mediated via the pro-inflammatory transcription factor, nuclear factor-κB (NF-κB). Knockdown studies have shown that lncRNAs tend to act in trans to regulate the expression of multiple inflammatory mediators and other responses. Mechanistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 102 publications
(158 reference statements)
1
77
0
Order By: Relevance
“…Knockdown of lincRNA-Cox2 resulted in impaired production of proinflammatory genes (i.e., IL-6), while IFNrelated genes were hyperactivated in the absence of lincRNA-Cox2 [42][43][44][45][46]. Numerous other studies have made use of the TLR-signaling biological system, uncovering and characterizing dozens of novel lncRNAs that act in a wide range of mechanisms to either positively or negatively regulate this pathway as reviewed in Carpenter et al and Hadjicharalambous et al [47,48].…”
Section: The Biological Questionmentioning
confidence: 99%
See 2 more Smart Citations
“…Knockdown of lincRNA-Cox2 resulted in impaired production of proinflammatory genes (i.e., IL-6), while IFNrelated genes were hyperactivated in the absence of lincRNA-Cox2 [42][43][44][45][46]. Numerous other studies have made use of the TLR-signaling biological system, uncovering and characterizing dozens of novel lncRNAs that act in a wide range of mechanisms to either positively or negatively regulate this pathway as reviewed in Carpenter et al and Hadjicharalambous et al [47,48].…”
Section: The Biological Questionmentioning
confidence: 99%
“…These are just two examples of lncRNAs that have provided critical insights into the roles of lncRNAs in immunity. For more information on specific lncRNAs that are involved in innate immunity we direct you to the following recent reviews on this topic [42,47,63]. In addition to these bulk RNA sequencing studies, a small number of single cell RNA sequencing studies have been performed in both human and mouse that can be utilized to examine differential expression of lncRNAs in basal versus treatment conditions or between cell types [64][65][66][67][68].…”
Section: Trans Regulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, patients with eosinophilic esophagitis, an allergic inflammatory disorder, have altered lncRNA profiles (Sherrill et al, 2014), and altered lincRNA expression has been identified in CD8+ T cells of severe asthma patients (Tsitsiou et al, 2012). lincRNAs are involved in the innate immune response, including activation of monocytes and macrophages as well as regulating expression of inflammatory genes (Hadjicharalambous and Lindsay, 2019), highlighting potential pathways through which lincRNAs may mediate allergenic responses. However, few studies have examined lncRNAs with regards to HDM allergens.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, due to the lack of mechanistic studies, lncRNAs are mainly grouped according to their proximity to protein coding genes. The most significant groups are lincRNAs (long intergenic non-coding RNAs), antisense, intronic, enhancers, and pseudogenes [106]. Although these transcripts are generally poorly evolutionary conserved [107], it is now evident that they hold a critical role in multiple biological pathways, including the modulation of several developmental processes and pathophysiological states [104,108], by regulating transcription of protein coding genes via a variety of mechanisms.…”
Section: Long Non-coding Rnasmentioning
confidence: 99%